2011
DOI: 10.1103/physrevd.84.023511
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cosmological dual to inflation

Abstract: We derive all single-field cosmologies with unit sound speed that generate scale invariant curvature perturbations on a dynamical attractor background. We identify three distinct phases: slow-roll inflation; a slowly contracting adiabatic ekpyrotic phase, described by a rapidly-varying equation of state; and a novel adiabatic ekpyrotic phase on a slowly expanding background. All of these yield identical power spectra. The degeneracy is broken at the 3-point level: unlike the nearly gaussian spectrum of slow-ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…Initially |t| ≫ |t * | and M b (t * − t) b ≫ 1, the universe is slowly expanding [20], [21], [22], see [31], [32] for alternatives. Here,…”
mentioning
confidence: 99%
“…Initially |t| ≫ |t * | and M b (t * − t) b ≫ 1, the universe is slowly expanding [20], [21], [22], see [31], [32] for alternatives. Here,…”
mentioning
confidence: 99%
“…The similar idea was also proposed by Wetterich [14,15] for different motivation. The scale-invariant curvature perturbations can also be obtained during the slow contraction (ǫ ≫ 1), i.e., in ekpyrotic universe [16,17], by applying adiabatic ekpyrosis mechanism [18,19], though for ekpyrotic universe the entropic mechanism is actually better to explain the observation [20][21][22].…”
Section: Jhep03(2016)134mentioning
confidence: 99%
“…In this model the universe slowly transitions from expansion to contraction. But unlike in [9], here we describe the apex model as a distinct mechanism that is independent from the adiabatic ekpyrotic slow expansion. When the universe gradually stops expansion to reach an apex, the scale factor a slowly comes to a halt, and the Hubble parameter H has to drop from positive to zero.…”
Section: Flow Parametersmentioning
confidence: 99%
“…We have shown that the adiabatic ekpyrotic mechanism takes place near the point (0, 0) on the p > 0 side. Notably, this fixed point may also be approached from the p < 0 side, which corresponds to a slow expansion [9,18] that produces scale invariant perturations in a similar way.…”
Section: Flow Parametersmentioning
confidence: 99%
See 1 more Smart Citation